HUBUNGAN FUNGSI KELUARGA DENGAN KUALITAS HIDUP PASIEN STROKE - Mufidah, Nisfil; Wahyudi, Rahmad; Rosalinda, Rosalinda (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Stroke is a disease that affects the entire body such as paralysis, cognitive function deficits, speech difficulties, emotional difficulties, pain and problems in daily life which then causes patients to experience a decrease in quality of life. The results of a preliminary study conducted at ANNA Medika Madura General Hospital with 10 respondents found that 6 people experienced quality of life with poor criteria. The purpose of this study is to analyze the relationship between family function and quality of life of stroke patients in the working area of ANNA Medika Madura General Hospital. This study used correlation analytical research method with cross sectional approach. The population of stroke patients was 35 people with a sample of 32 respondents. The independent variables was family function and the dependent variables was quality of life of stroke patients. The sampling technique used simple random sampling with APGAR and WHOQOL-BREF questionnaire instruments. Test statistics using the Spearman Rank test. The results obtained P Value: 0.000 means that there was a relationship between family function and the quality of life of stroke patients. As for the results of the Correlation Coefficient or r: 0.835 which means there was a very strong relationship between family function and the quality of life of stroke patients. Further researchers are expected to develop research with a larger sample and can develop other variables. For respondents, it is expected to improve family functions to improve the quality of life of patients during treatment and treatment.